Soil clays : linking geology, biology, agriculture, and the environment - Churchman, G. J.; Velde, B. (Bruce) (Boca Raton : CRC Press, 2019)
"This book aims to help improve predictions of important properties of soils through a modern understanding of their highly reactive clay minerals as they are formed and occur in soils worldwide. It examines how clays occur in soils and the role of soil clays in disparate applications"--
Introduction and definitions -- Soil clays : mineralogy -- Geology : defining the starting point for soil and clay formation -- Primary minerals and their alteration by weathering -- Driving forces of alteration -- Chemistry of alteration by weathering -- Formation of clays in the soil zone of alteration -- Nature and origin of surface soil clays -- The importance of climate in the formation of soil clays -- Associations of soil clays -- Occurrence and extraction of soil clays -- Identification and quantification of clay minerals in soils -- Surfaces, surface reactions, and particle size effects -- Role of soil clays in agriculture, the environment, and society -- Summary.
OCLC-licensed vendor bibliographic record.
Keywords: Clay soils; Clay; Soils; Soil mineralogy; TECHNOLOGY & ENGINEERING / Engineering (General); TECHNOLOGY & ENGINEERING / Reference; TECHNOLOGY / Agriculture / General; NATURE / Environmental Conservation & Protection; SCIENCE / Life Sciences / Botany